A comparison of needle-free and needle injection methods and solutions for enhancement of beef Longissimus lumborum muscles - Crow, Brett Alan (Kansas State University, 2009)
Objectives were to determine the effects of needle-free (NF) versus needle (N) injection methods and/or solutions for enhancement of beef longissimus lumborum muscle (LM) on color, instrumental tenderness, sensory attributes, pump yields, and cooking losses. In experiment 1, LM (n=15) at 9 d postmortem were halved before random assignment to N or NF injection enhancement with a solution containing 2.2% salt, 4.4% sodium tripolyphosphate (STPP), and 1.5% K lactate. Different steaks from each loin half were either placed on a 5 d color display, frozen for later sensory analysis, or aged until d 13 postmortem for LM slice shear force measurements. Pump yields tended (P=0.08) to be higher for NF injection. Needle injected steaks were darker (P<0.05) on day 1, but not after that. Discoloration was not different (P>0.05) between treatments. The NF treatment had greater (P<0.05) instrumental tenderness and intensity of off-flavors but less (P<0.05) cooking loss and beef flavor. In Experiment 2, LM (n=28) at 5 d postmortem were halved before random assignment to one of four treatments: 1) N, or 2) NF injection with a solution containing 2.2% salt, 4.4% STPP, 15% K lactate, and 0.58% rosemary; 3) N, or 4) NF injection with a solution containing 2.4% Ca lactate and 0.58% rosemary. Steaks from each loin half were either frozen for later sensory analysis or aged until d 14 postmortem for LM slice shear force measurements. Loins phosphate enhanced with the NF injector had the highest (P<0.05) pumped yields with no differences (P>0.05) among other treatment combinations. Instrumental tenderness was not different (P>0.05) between N and NF treatments but was higher with the phosphate solution than the Ca lactate solution. The NF treatment had lower (P<0.05) cooking losses when the phosphate solution was used, which resulted in less (P<0.05) cooking loss than the Ca lactate solution. More (P<0.05) off-flavors and abnormal texture resulted from NF injection. The phosphate solution resulted in greater (P<0.05) myofibrillar and overall tenderness, juiciness, off-flavors and abnormal texture with less (P<0.05) connective tissue than the Ca lactate solution. Enhancing beef LM with a phosphate solution and NF injection might improve yields, tenderness, and juiciness while harming texture and flavor.
Keywords: Beef; Injection enhancement; Needle-free; Needle; Phosphate; Calcium lactate; Agriculture, Animal Culture and Nutrition (0475)